Socio-Demographics Factors Influencing Parental Knowledge About Childhood TB - Putri, Azalia Melati; Rakhmawati, Windy; Maryam, Nenden Nur Asriyani; Hendrawati, Sri (Journal of Nursing Care, 2023)
Knowledge is a fundamental aspect that can influence attitudes and behaviour in seeking parental health services and have an impact on reducing the scope of finding cases of TB in children. The eastern region of Bandung Regency is a densely populated area with a low socioeconomic level and has a high number of TB cases. Knowledge is known to be related to behavior in seeking health services and is one of the factors that influence the behavior of parents who have children with TB. This study aims to determine the relationship between socio-demographic factors that can influence parents' knowledge about TB in children. This research with a correlational descriptive design was carried out using purposive sampling with the criteria of a sample of parents who have children aged 0-14 years and are undergoing TB treatment in the eastern region of Bandung Regency in the 2020–2022-year range. The number of samples involved in this research was 54 people. The questionnaire used in this study was based on the Knowledge, Attitudes and Practice (KAP) survey guidelines developed by the World Health Organization. Bivariate data analysis was performed using contingency correlation test. Most parents already have good knowledge about TB (57.4%). Age (p=0.019) is a factor related to parents' knowledge about child TB. Unrelated factors were education (p=0.064), economy (p=0.425), and parents' occupation (p=0.272). The knowledge of parents who have children with a history of TB in the Eastern Region of Bandung Regency regarding childhood Tuberculosis is quite good. This can be influenced by aspects of education, economics, and parents' work. Health workers play a major role in increasing parental knowledge about child TB. Nurses as care givers and educators can involve parents in the process of caring for childhood TB patients and increase knowledge through education and health promotion about TB.